2019
DOI: 10.1158/1538-7445.sabcs18-p6-02-12
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-02-12: Artificial Intelligence over thermal images for radiation-free breast cancer screening

Abstract: Introduction: Breast cancer is the largest cause of cancer deaths in women today. NIRAMAI has developed a novel solution for detecting early stage breast cancer in women of all age groups. It is low cost, non-contact and portable solution. This radiation-free solution also works on dense breasts and hence is applicable beyond developing countries. The core of the solution is a Computer Aided Diagnostics engine called Thermalytix, which uses Artificial Intelligence algorithms on high resolution thermal images. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our own earlier research on using machine learning for breast thermography has shown promising accuracy results [20][21][22][23]. In [20], we described the effectiveness of medically interpretable imaging features obtained from the abnormal thermal patterns to get high levels of sensitivity and specificity of interpretation.…”
Section: Role Of Machine Learning In Thermal Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our own earlier research on using machine learning for breast thermography has shown promising accuracy results [20][21][22][23]. In [20], we described the effectiveness of medically interpretable imaging features obtained from the abnormal thermal patterns to get high levels of sensitivity and specificity of interpretation.…”
Section: Role Of Machine Learning In Thermal Imagingmentioning
confidence: 99%
“…In [21], we proposed the use of shape-based and temperature-based image processing features to detect the vasculatures from thermal images. These algorithms have shown comparable and sometimes better results than standard of care [22,[21][22][23].…”
Section: Role Of Machine Learning In Thermal Imagingmentioning
confidence: 99%